2021
DOI: 10.1089/whr.2021.0044
|View full text |Cite
|
Sign up to set email alerts
|

Fertility Preservation and Infertility Treatment in Medical Training: An Assessment of Residency and Fellowship Program Directors' Attitudes

Abstract: Background: Given the concurrence of medical residency and fellowship training with typical childbearing years, trainees often must make difficult decisions regarding family planning, requiring the support of their residency and fellowship program directors (PDs) to guide them. Objective: Our hypothesis was that PDs have knowledge gaps and varying levels of support in terms of their trainees' fertility, and the goal of our study was to assess the knowledge and support o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 39 publications
1
2
0
Order By: Relevance
“…found that 21.0%–41.0% of programs offered paid parental leave, while 46.0% required make‐up time 24,25 . Maternity and paternity leaves ranged from 1 to 8 weeks for female trainees, 5,16,25 which is similar to a previous report of 6–8 weeks in a study encompassing 299 PDs from all medical specialties 33 . Nguyen et al.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…found that 21.0%–41.0% of programs offered paid parental leave, while 46.0% required make‐up time 24,25 . Maternity and paternity leaves ranged from 1 to 8 weeks for female trainees, 5,16,25 which is similar to a previous report of 6–8 weeks in a study encompassing 299 PDs from all medical specialties 33 . Nguyen et al.…”
Section: Discussionsupporting
confidence: 78%
“…24,25 Maternity and paternity leaves ranged from 1 to 8 weeks for female trainees, 5,16,25 which is similar to a previous report of 6-8 weeks in a study encompassing 299 PDs from all medical specialties. 33 Nguyen et al found the duration of leave to vary at the different levels of training, where residents had the lowest and practicing surgeons had the highest time off. 19,20 In a study of surgical residents, T A B L E 3 Obstetric complications and risks.…”
Section: Discussionmentioning
confidence: 99%
“…This study brings a new lens to the previously published work. Participants noted delaying milestones, including starting a family, which may already be fraught during training [ 34 ], as well as impacts on childrearing, previously explored by Spruce and colleageus [ 35 ]. While Lyndon, Jenkins and their colleagues noted the stress related to assessment [ 13 , 14 ], our participants went further, delineating a relationship between their success, their career, and stigma associated with failure, which may all be perpetuated in the hidden curriculum.…”
Section: Discussionmentioning
confidence: 99%